2020
DOI: 10.1186/s40001-020-00417-2
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave lithotripsy, for the treatment of kidney stones, results in changes to routine blood tests and novel biomarkers: a prospective clinical pilot-study

Abstract: Background: The number of patients undergoing shock wave lithotripsy (SWL) for kidney stones is increasing annually, and as such the development of post-operative complications, such as haematuria and acute kidney injury (AKI) following SWL, is likely to increase. The aim of the study was to evaluate changes in routine blood and novel biomarkers following SWL, for the treatment of kidney stones. Methods: Twelve patients undergoing SWL for solitary unilateral kidney stones were recruited. From patients (8 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…Interestingly, Plasma IL-10 concentrations significantly increased following TTPB. Our data differ from Hughes et al [37], who reported no significant changes to IL-10 concentrations post-operatively following shock wave lithotripsy (SWL), non-invasive urological procedure performed to treat small kidney stones. Normally, IL-10 is considered to have potent anti-inflammatory properties, but increased levels have been reported to be associated with infection.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Plasma IL-10 concentrations significantly increased following TTPB. Our data differ from Hughes et al [37], who reported no significant changes to IL-10 concentrations post-operatively following shock wave lithotripsy (SWL), non-invasive urological procedure performed to treat small kidney stones. Normally, IL-10 is considered to have potent anti-inflammatory properties, but increased levels have been reported to be associated with infection.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study found a significant increase in plasma IL-6 concentrations at 120 min and 240 min post-TTPB, which follows a similar pattern of change as reported after transurethral resection of the prostate (TURP) [36] and shock wave lithotripsy for kidney stones [37], suggesting an immune and stress (inflammatory) response to the procedure.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…7 Its importance is appreciated that annually in USA about 1 million affected individuals are treated through ESWL. 16 ESWL technique preferred for the treatment of kidney stone that range between 4 mm and 2cm (size). 17 On the other hand, PCNL was established to lessen the morbidity and mortality linked with open kidney procedures, and it is still the primary management for significant kidney stones today.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that stone formers have twice as high a risk of chronic renal disease than non-stone formers. Pediatric kidney stone is increasing in incidence and healthcare costs as well as putting an increasing clinical and budgetary strain on the world's healthcare systems (Hughes et al, 2020). As a result, this problem needs necessitated strategies to optimize the treatment of children with kidney stones and to reduce recurrence risk through preventive medical and dietary management.…”
Section: Significance Of the Studymentioning
confidence: 99%